Hubungan Persepsi Pengembangan Karir Dengan Kinerja Karyawan PDAM Cabang Medan Kota - Sembiring, Afulina; Azis, Azhar (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2024)
This research aims to determine the relationship between perceptions of career development and the performance of PDAM Medan City Branch employees. This research method uses a quantitative approach. The population consists of 35 employees with a total sampling sample. The research instrument was a modified Likert scale for perceptions of career development (29 valid items out of 32) and employee performance (42 valid items out of 48). Data analysis was carried out using Pearson correlation (p 0.05) with the help of SPSS 20 for Windows after testing the assumptions of normality and linearity. The results of data analysis show that there is a significant positive relationship between perceptions of career development and employee performance at PDAM Medan City Branch. The Pearson product moment correlation analysis method shows a correlation coefficient (r) of 0.986 with a significance value (p) of 0.000, which indicates that the higher the perception of career development, the higher the employee's performance. These findings support the research hypothesis which states that perceptions of career development positively influence employee performance. In addition, the coefficient of determination (r^2) of 0.972 shows that perceptions of career development are able to explain variations in employee performance by 97.2%.